Intermix of metal nanoparticles-single wall carbon nanotubes. - Xu, F; Lu, Q; Ye, L; Tsang, S (Royal Society of Chemistry, 2017)
Using physical mixtures of Pd/SWNTs (Pd nanoparticles on single-walled carbon nanotubes) and Pt/SWNTs, the composites show electro-catalytic properties comparable to the corresponding alloys: electron exchange readily occurs between the two metal nanoparticles via SWNT support at long ranges without direct atomic contact, which is responsible for the tunable alloy-like properties.